Woo : awakening teenagers' desire to follow in the way of Jesus - Schmidt, Morgan (San Diego : Mark Oestreicher/The Youth Cartel, LLC, 2014)
What if teenagers wanted to follow Jesus, not just avoid hell? Desire makes us who we are. What teenagers want whether they possess it, long for it, are terrified by it, deny it, pursue it, or give up on it impacts their relationships, dictates their actions, forms their character, and shapes their beliefs. So if they actually want Jesus or the church or the kingdom, then they're more likely to keep wanting their faith beyond youth group. Woo connects teenagers good desires with the Good News. It's an invitation to reimagine the church as a place where students' desires are honored; where they will encounter the One who desires and can participate with God in restoring the world. Woo isn't another method or gimmick that will bring students flocking to youth group. Instead, it suggests a way of being one that begins with us. This isn't sexy youth ministry, but it's good.
Includes bibliographical references (pages 225-227).
Keywords: Church work with teenagers; Church work with youth; Christian teenagers -- Religious life